2018
DOI: 10.1186/s40409-018-0167-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration inhibition activity of a non-RGD disintegrin from Crotalus durissus collilineatus venom

Abstract: BackgroundIn recent decades, snake venom disintegrins have received special attention due to their potential use in anticancer therapy. Disintegrins are small and cysteine-rich proteins present in snake venoms and can interact with specific integrins to inhibit their activities in cell-cell and cell-ECM interactions. These molecules, known to inhibit platelet aggregation, are also capable of interacting with certain cancer-related integrins, and may interfere in important processes involved in carcinogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…In this context, this study indicated that GNP-NN 32 was capable of inducing apoptosis at a concentration of 1.5 μg/mL in MCF-7 cell line and 5 μg/mL in MDA-MB-231 cell line. Our results are in agreement with other studies that discovered that disintegrin from Crotalus durissus collilineatus venom induced cytotoxicity [37] whereas BthTX-I from Bothrops jararacussu induced apoptosis [38] and also showed antitumor and antimetastatic effects [39] on human breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…In this context, this study indicated that GNP-NN 32 was capable of inducing apoptosis at a concentration of 1.5 μg/mL in MCF-7 cell line and 5 μg/mL in MDA-MB-231 cell line. Our results are in agreement with other studies that discovered that disintegrin from Crotalus durissus collilineatus venom induced cytotoxicity [37] whereas BthTX-I from Bothrops jararacussu induced apoptosis [38] and also showed antitumor and antimetastatic effects [39] on human breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…The antineoplastic potential of snake venom disintegrins have been shown in several studies, e.g. contortrostatin (disintegrin isolated from Agkistrodon contortrix venom) [23], saxatilin (disintegrin from Gloydius saxatilis venom) [24], PAIEM (disintegrin isolated from Echis multisquamatis venom) [25] and a disintegrin from Crotalus durissus collilineatus venom [26]. The disintegrins act by inhibiting angiogenesis, invasion and migration of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, were performed in normoxia only. Non-RGD disintegrins from Crotalus durissus colineatus inhibited MDA-MB-231 migration in a wound healing assay after 24 h in normoxia [61].…”
Section: Discussionmentioning
confidence: 97%